Karakteristik Pasien Luka Bakar di RSU Haji Medan Periode 2022-2024 - Febrini, Dewi; Evangelia, Shanty; Henny, Henny (Jurnal Pendidikan Indonesia, 2025)
This study aims to describe the characteristics of burn patients treated at Medan Haji Hospital from 2022 to 2024. Data were collected from medical records, covering age, gender, cause of burn, degree of burn, and burn area. The results showed that the age group 12-16 years had the highest incidence of burns (36.1%), with females (52.8%) being more affected. The main cause of burns was fire (51.1%), followed by hot water (21.7%), electricity (16.1%), and chemicals (11.1%). Most of the burns were classified as degree II B (35.6%) and degree II A (33.9%). The majority of burn cases had an area of more than 10% of the body, with 43.3% having an area larger than 20%. The study also found a significant relationship between the cause of the burn and the degree and size of the burn. These findings provide essential information to enhance burn prevention and treatment efforts, especially for vulnerable age groups and common causes.